Association Between Knowledge Level and Pain Self-Medication Behavior Among Residents of Sabungan Nihuta IV Village, Sipahutar District, North Tapanuli - Kasan, Harsan Arifin; Lestari, Meliani Dwi; Siburian, Elsa (Pustaka Media Publishing, 2026)
Self-medication is a common practice, particularly in rural areas with limited access to healthcare services. Analgesics are among the most frequently used medications for pain management; however, inappropriate use may lead to drug-related problems due to insufficient knowledge. This study aimed to analyze the relationship between knowledge level and pain self-medication behavior using analgesics among residents of Sabungan Nihuta IV Village, Sipahutar District, North Tapanuli Regency. This research employed a quantitative cross-sectional design with a sample of 78 respondents selected using cluster random sampling. Data were collected through questionnaires and analyzed using the Spearman correlation test. The results showed that most respondents had a good level of knowledge (79%), while the majority demonstrated moderate self-medication behavior (54%). Statistical analysis revealed a significant relationship between knowledge level and self-medication behavior (p = 0.000 < 0.05). In conclusion, knowledge level is significantly associated with self-medication behavior. Strengthening community education is necessary to promote rational, safe, and responsible use of analgesics.